Immunologic unresponsiveness to alloantigen in vivo: a role for regulatory T cells. - Wood, K; Bushell, A; Jones, N (2011)
Exposure to alloantigen in vivo or in vitro induces alloantigen reactive regulatory T cells that can control transplant rejection. The mechanisms that underpin the activity of alloantigen reactive regulatory T cells in vivo are common with those of regulatory T cells that prevent autoimmunity. The identification and characterization of regulatory T cells that control rejection and contribute to the induction of immunologic unresponsiveness to alloantigens in vivo has opened up exciting opportunities for new therapies in transplantation. Findings from laboratory studies are informing the design of clinical protocols using regulatory T cells as a cellular therapy.